INVESTING IN THE GLOBAL ENERGY: KEY TRENDS - A. Stepanova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The questions of energy investments in the regions of the world, which allowed to carry out analysis of various types of energy production, focus on enerhozberezheni and renewable energy sources. Proved the importance of investing energy sector for the entire civilized world and defined the priorities of the process. Indicated that investment in the energy sector is based on public policy, to determine possible solutions to the energy dependence of Ukraine, taking into account the international experience.